Emotional Intelligence, Leadership, Governance and Management Strategy: Key Drivers of Business Sustainability in Engineering Services - Marirajan Murugan; M. N. Prabadevi (Qubahan Academic Journal)
Purpose: The paper deals with plant engineering services based on global engineering standards and it aim to meet the project budget and timeline by minimizing unproductive hours, obtaining design inputs for the design and procurement, compromising quality and sharing resources. This research paper aims to explore the business sustainability of engineering service companies in the Gulf Cooperation Council (GCC) countries. Design and methodology: In order to gather information for this research, researchers have gathered data from twenty-three (23) engineering services companies that have received approval to provide engineering services to oil and gas operating companies across the Gulf Cooperation Council (GCC). Researchers have then used XLSTAT version 2024.2.2 to analyze the data. Findings: Researchers found a strong correlation between an entrepreneur's emotional intelligence, leadership abilities, governance, and management strategy and the business sustainability of their organization. Research, Practical & Social Implications: According to researchers, the primary aspect contributing to the sustainability of the engineering services industry, is resource use. Building solid business relationships requires emotional intelligence on the part of entrepreneurs, and the sustainability of the company is largely dependent on how these relationships are managed. In order to improve their management strategy-based business sustainability, entrepreneurs require high emotional intelligence and strong leadership abilities. Main limitation of this study is, the study focuses only in GCC countries. Originality/Value: To the best of the author's knowledge, this study, which focuses on emotional intelligence, leadership abilities, governance, and management strategy, may be the first to look into the business sustainability of engineering service companies.